A needs analysis on challenges in English expository writing among English as a second language learners - Zakaria, Noorfatin; Sulaiman, Nur Ainil (Institute of Advanced Engineering and Science, 2025)
Effective communication in English, particularly in writing, is becoming increasingly important globally. Despite being exposed to all four language skills, English as a second language (ESL) learners regularly perceive writing to be the most difficult element. This stance is held by both the English education system and ESL students in Malaysia, highlighting the importance of writing as an important language skill that is difficult to acquire. With expository writing is seen to be the least researched genre, this research seeks to fill this gap by examining the challenges ESL learners face in writing expository essays to provide potential classroom solution to improve their writing skill in this genre. A questionnaire was administered to 68 Form Four ESL learners as part of this study to gather essential data. The collected data underwent analysis using descriptive statistics with the statistical package for the social sciences (SPSS Ver. 27). The results were then presented in frequencies, percentages and the overall mean score. The findings revealed that respondents are still struggling with content development and organization as well as the writing process. Therefore, adding more interactive and student-centered learning approaches to ESL writing lessons could help students’ writing skills.